(3GdSQGL GdefjQ aj TQM eYQGL GdHTjQ GdfPjQs - (3Ydj Hf YHO GdbGOQ GdfHJjJi GdMfajs; (3eMeO Hf CMeO Hf Ydj GdScfOQj GdZjWj GdTGaYj, CHh GdehGgH, fLe GdOjf,J (B981 (3g` s ((3GdLGeY GdCRgQ s)
(3ChdgG (B:s
(3hHYO GYde Cf GdESQGA Hg Udi Gddg Ydjg hSde hQbjg Edi CYdi GdSehGJ ef CYXe GdHjfGJ FhddYdeGA ai gPG GdTCf eYGQjM hdeG JOGhd Hjf CjOi GdfGS CQOJ Cf CTQMg HeG jRjd Yfg GdCTcGd hGdEdJHGS s
(3BNQgG (B:s
(3hcGf GdaQGZ ef gPG GdTQM UHjNI jhe GdCMO SGOS YTQ QHjY GdKGfi SfI SHY hCQHYjf hCda HGdLGeY GdCRgQ s
(3heYQGL GdHTjQ GdfPjQ dfLe GdOjf eMeO Hf CMeO Hf Ydis
(3GdeJhai SfI (B984(3g`s
(3hgfGc Tc ai Cf eDda GdeNWhW gh fGSNgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs